The bioclimatic design of schools: An efficient device for protecting environment and children’s health - Fercha, Nessma; Benbouaziz, Akila (Journal of Architecture and environment of child, 2021)
With the urgent need today to reduce energy consumption, face environmental degradation, and control the environmental impacts of school buildings, it becomes essential to move towards environmentally friendly designs called bioclimatic architectures. Then there The bioclimatic schools are considered today one of the effective mechanisms for the protection of the environment and the health of the child, because it contributes to eliminate the environmental and psychological problems of the schoolchildren in particular the children, these fragile creators who is strongly exposed to the various phenomena of pollution of which its city suffers. In fact, the child being a developing individual and more sensitive, he is dependent on the environment that surrounds him and this makes him vulnerable. he has the right to be integrated in a healthy and comfortable environment and will guarantee him a prosperous life in his environment. Indeed, At birth and during childhood, the human being is particularly sensitive to the conditions of the environment in which he lives.